Cyber Extortion as a Cybercrime in Indonesian Criminal Law: Normative Analysis and Legal Protection for Victims - Rahul Sihombing; Sachila Fattah; Dirga Arya Kesuma Nasution; Rosmalinda; Annisa Hafizah (Catalist Indo Publisher, 2026)
This study aims to analyze the legal regulation of Cyber Extortion within the Indonesian criminal law system and examine the forms of legal protection and criminal liability applicable to perpetrators and victims. The research employs a juridical-normative method with a descriptive qualitative approach. Primary legal materials include Article 368 of the Criminal Code, Article 45 in conjunction with Article 27B of Law No. 1 of 2024 concerning the Second Amendment to the ITE Law, and Law No. 44 of 2008 concerning Pornography, supported by relevant legal doctrines and court practices. The findings indicate that Indonesian positive law has established a relatively comprehensive normative framework for addressing Cyber Extortion. Judicial interpretation has expanded the concept of “violence or threat of violence” to encompass psychological threats in cyberspace, including threats to disseminate sensitive data that may damage a victim’s reputation. Cyber Extortion can be categorized based on the relationship between perpetrators and victims, including both prior face-to-face relationships and purely online interactions. Legal protection mechanisms include the right to report, personal data protection, fair trial guarantees, restitution, and psychological assistance. Criminal liability is grounded in the principle of fault, particularly intentional conduct, with sanctions ranging from six months to twelve years imprisonment. In conclusion, effective implementation still requires stronger inter-agency coordination and increased public awareness to enhance prevention and victim protection.